Investigation of optical soliton solutions for the perturbed Gerdjikov-Ivanov equation with full-nonlinearity - Onder, Ismail; Secer, Aydin; Ozisik, Muslum; Bayram, Mustafa (CELL PRESS, 2023)
We have discussed the perturbed Gerdjikov-Ivanov (pGI) equation describing optical pulse propagation (PP) with perturbation effects, which has various applications in optical fibers, especially in photonic crystal fibers. According to our literature review, we have discovered new and original soliton types using the Sardar sub-equation and the modified Kudryashov methods, which have not been applied to this model before. We obtained dark, bright, periodic-singular and periodic-M-shaped soliton solutions, respectively. The analytical forms of the obtained solutions are represented by 3D, 2D and contour graphics. In addition, the physical effects of the solution parameters on the wave envelope have been described and clearly interpreted by presenting their 2D graphics.
Keywords: Perturbed Gerdjikov-Ivanov equation; Sardar subequation method; Modified new Kudryashov method; Optical solitons; SCHRODINGER-EQUATION; Science & Technology - Other Topics